A degradable film material and preparation method thereof
By mixing the quinone extract with chitosan, glycerin and organic acid aqueous solution, a chitosan-based degradable packaging material with a low water absorption rate is prepared, which solves the problem of high water absorption of chitosan-based materials, realizes multiple performance optimization of the material, and the preparation method is environmentally friendly and safe.
Patent Information
- Application Number
- CN202310176869.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The water absorption of chitosan-based degradable packaging materials is too high, resulting in easy damage to the material and it is difficult to maintain good biodegradability, tensile performance of fracture, antioxidant performance, water vapor permeability and ultraviolet barrier properties at the same time.
The degradable membrane material is prepared by mixing the quinone extract with chitosan, glycerin and organic acid aqueous solution. The quinone extract is prepared by ultrasonic extraction and spin drying. Reasonable ratio and preparation method can significantly reduce the water absorption rate.
It effectively reduces the water absorption rate of chitosan-based degradable packaging materials, while maintaining good biodegradable properties, tensile breaking properties, antioxidant properties, water vapor permeability and ultraviolet barrier properties, and the preparation method is simple, safe and green.
Smart Images

Figure CN116376073B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, and in particular to a degradable film material and a preparation method thereof. Background Art
[0002] Food packaging waste is increasing, and non-biodegradable materials such as plastics account for a large proportion of the food packaging market, making biodegradable food packaging technology that is beneficial to the environment and human health a research and development trend. Biopolymers have been proven to be ideal substrates for degradable materials. Among degradable biopolymers, chitosan has good film-forming ability, is non-toxic and harmless, has a wide range of sources, and is cheap, so it has broad application prospects.
[0003] However, the water absorption of chitosan-based degradable packaging materials is too high, which makes the packaging materials easy to be damaged. Therefore, how to develop a chitosan-based degradable packaging material with low water absorption and good biodegradability, tensile strength at break, antioxidant properties, water vapor permeability, and ultraviolet blocking properties has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] First, the present invention provides a method for preparing a degradable film material, comprising:
[0005] Mixing chitosan, gallnut extract, glycerin and an organic acid aqueous solution to prepare a degradable membrane material solution; then pouring the degradable membrane material solution into a mold and drying it to obtain a degradable membrane material solution;
[0006] Wherein, the preparation method of the gallnut extract comprises:
[0007] The gallnut and the alcohol solution are mixed in a ratio of 1 g: 8-12 mL, placed at 70-80° C. for more than 40 minutes, and then ultrasonically extracted for 25-35 minutes; after filtering, the filtrate is spin-dried to obtain a gallnut extract; the concentration of the alcohol solution is 75-85%.
[0008] The present invention finds that the degradable film material prepared by the above preparation method can effectively reduce the water absorption rate of the chitosan-based degradable packaging material. Among them, the gallnut extract obtained by the above extraction method can significantly reduce the water absorption rate while enabling the degradable film material to still maintain good biodegradability, tensile strength at break, antioxidant properties, water vapor permeability, ultraviolet blocking performance and low moisture regain.
[0009] In some embodiments, in the method for preparing the gallnut extract, the extraction is repeated more than three times, the extracts are combined, and the filtrate is filtered and then dried to obtain the gallnut extract.
[0010] Preferably, the alcohol solution is an ethanol solution.
[0011] In some embodiments, the mixture is placed at 70-80° C. for more than 60 minutes.
[0012] It is preferably placed at 74-78°C for more than 60 minutes.
[0013] In some embodiments, the weight ratio of chitosan to the Galla chinensis extract is 1:0.1-0.3.
[0014] Preferably, the weight ratio of chitosan to the gallnut extract is 1:0.2-0.3;
[0015] More preferably, the weight ratio of chitosan to the gallnut extract is 1:0.25-0.3.
[0016] Under the above ratio, the comprehensive performance of the prepared degradable film material reaches the best.
[0017] In some embodiments, the weight ratio of chitosan to glycerol is 1:0.1-0.3.
[0018] In some embodiments, the weight ratio of chitosan to organic acid is 1:0.4-0.8.
[0019] In some embodiments, the concentration of the organic acid in the aqueous solution of the organic acid is 0.5 to 1.5%.
[0020] In some embodiments, in the method for preparing the gallnut extract, the gallnut is crushed into powder and then mixed with the alcohol solution.
[0021] In some embodiments, the organic acid is acetic acid.
[0022] Furthermore, the present invention also provides a degradable film material, which is prepared by the preparation method in any of the above embodiments.
[0023] Furthermore, the present invention also provides application of the above-mentioned degradable film material in the field of packaging materials.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention utilizes the gallnut extract to develop a chitosan-based degradable packaging material with low water absorption, and has good biodegradability, tensile strength at break, antioxidant property, water vapor permeability, ultraviolet blocking property and low moisture regain.
[0026] In addition, the preparation method of the present invention is simple, safe and green, and has good application prospects in food storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1This is a graph of the antioxidant function test results provided by the present invention.
[0028] Figure 2 This is a graph of mechanical property test results provided by the present invention.
[0029] Figure 3 This is a graph showing the test results of the ultraviolet blocking performance provided by the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] If no specific techniques or conditions are specified in the examples, all are carried out according to conventional methods or the techniques or conditions described in the literature in the field, or according to the product instructions. If no manufacturer is specified for the reagents and instruments used, all are conventional products that can be purchased through regular channels.
[0032] The preparation method of the gallnut extract in the following embodiment is:
[0033] (1) using a pulverizer to grind the Chinese gallnut into powder;
[0034] (2) Add 50 mL of 80% ethanol water to 5 g of gallnut powder, place at 76°C for 1 h, perform ultrasonic extraction for 30 min, repeat the extraction three times, and combine the extracts;
[0035] (3) Filter the gallnut extract, and spin-dry the filtrate to prepare the gallnut extract.
[0036] Control group
[0037] This control group provides a degradable film material, and the preparation method is as follows:
[0038] (1) Weigh 3 g chitosan and 0.45 g glycerol;
[0039] (2) adding 200 mL of 1% acetic acid aqueous solution and stirring at room temperature to obtain a degradable membrane material solution;
[0040] (3) After removing bubbles from the degradable film material solution by ultrasonic treatment, the solution is added into a mold and dried to obtain a degradable film material named as cling film A.
[0041] Example 1
[0042] This embodiment provides a degradable film material, and the preparation method is as follows:
[0043] (1) Weigh 3 g chitosan and 0.45 g glycerol;
[0044] (2) Add 200 mL of 1% acetic acid aqueous solution and stir evenly at room temperature;
[0045] (3) adding 10% of the Chinese nut extract (based on the weight of chitosan) and stirring evenly to obtain a degradable membrane material solution;
[0046] (4) After removing bubbles from the degradable film material solution by ultrasonic treatment, the solution is added into a mold and dried to obtain a degradable film material, which is named as cling film B.
[0047] Example 2
[0048] This embodiment provides a degradable film material, and the preparation method is different from that of embodiment 1 only in that:
[0049] Adding 20% of Galla chinensis extract (based on the weight of chitosan);
[0050] The degradable film material was obtained and named as plastic wrap C.
[0051] Example 3
[0052] This embodiment provides a degradable film material, and the preparation method is different from that of embodiment 1 only in that:
[0053] Adding 30% of Galla chinensis extract (based on the weight of chitosan);
[0054] The degradable film material was obtained and named as fresh-keeping film D.
[0055] Comparative Example
[0056] This comparative example provides a degradable film material, and the preparation method is different from that of Example 3 only in that:
[0057] The preparation method of the gallnut extract is as follows:
[0058] (1) using a pulverizer to grind the Chinese gallnut into powder;
[0059] (2) Add 50 mL of 80% ethanol water to 5 g of gallnut powder, place at room temperature for 1 h, reflux extract for 30 min, repeat the extraction three times, and combine the extracts;
[0060] (3) Filter the gallnut extract, and spin-dry the filtrate to prepare the gallnut extract.
[0061] The degradable film material obtained in this comparative example is named comparative film.
[0062] Test Example 1 Water absorption test
[0063] (1) Cut the plastic wrap into small pieces of 30 mm × 40 mm, put them into a 50 mL beaker, place them in a forced air drying oven, set the temperature to 105 °C, and dry them for 24 h;
[0064] (2) Take out the plastic wrap, weigh its mass (M1, g), immerse the plastic wrap in deionized water for 10 min, and then centrifuge it at 5000 rpm for 10 min to remove excess water from the film;
[0065] (3) Take out the above-mentioned cling film, weigh its mass (M2, g), and calculate the water absorption. Repeat the measurement 3 times for each group.
[0066] Water absorption (%) = (M2-M1) × 100 / M2
[0067] The test results are shown in Table 1.
[0068] Table 1 Water absorption of cling film
[0069] sample Plastic wrap A Plastic wrap B Plastic wrap C Plastic wrap D Contrast film Water absorption (%) 80.65±0.55 71.99±0.64 56.89±0.58 54.74±0.74 75.34±0.28
[0070] The test results show that the cling film B, C, D has lower water absorption than the cling film A prepared with chitosan alone and the control film.
[0071] Test Example 2 Moisture regain test
[0072] (1) Cut the plastic wrap into small pieces of 30 mm × 40 mm, put them into a 50 mL beaker, place them in a forced air drying oven, set the temperature to 105 °C, and dry them for 24 h;
[0073] (2) Take out the plastic wrap, weigh its mass (M3, g), and place it in a constant temperature and humidity chamber at 21° C. and 65% relative humidity for 48 hours until constant weight is achieved;
[0074] (3) Take out the above-mentioned cling film, weigh its mass (M4, g), and calculate the moisture regain. Repeat the measurement 3 times for each group.
[0075] Moisture regain (%) = (M4-M3) × 100 / M3
[0076] The test results are shown in Table 2.
[0077] Table 2 Moisture regain of cling film
[0078] sample Plastic wrap A Plastic wrap B Plastic wrap C Plastic wrap D Contrast film Moisture regain (%) 16.68±0.81 14.32±0.07 12.56±0.22 10.69±0.18 15.43±0.36
[0079] The test results show that the cling film B, C, D have lower moisture regain than the cling film A prepared with chitosan alone and the control film.
[0080] Test Example 3 Biodegradability Test
[0081] (1) Cut the plastic wrap into small pieces of 40 mm × 40 mm, place them in a 50 mL beaker, place them in a forced air drying oven, set the temperature to 105 °C, and dry them for 24 h;
[0082] (2) Take out the above-mentioned cling film, weigh its mass (M5, g), and measure 25 mL of distilled water and pour it into the above-mentioned beaker. Immerse the dried cling film at room temperature for 24 hours. After draining the immersion liquid, place it in a forced air drying oven, set the temperature to 105° C., and dry it for 24 hours;
[0083] (3) Take out the above-mentioned plastic wrap, weigh its mass (M6, g), calculate the water solubility (WS), and repeat the measurement 3 times for each group.
[0084] WS%=(M5-M6)×100 / M5
[0085] The test results are shown in Table 3.
[0086] Table 3 Water solubility test results
[0087] sample Plastic wrap A Plastic wrap B Plastic wrap C Plastic wrap D Contrast film Water solubility (%) 21.29±1.82 24.51±1.06 35.73±1.27 36.58±1.92 23.47±1.09
[0088] The test results show that the water solubility of cling film B, C and D is higher than that of cling film A and the control film prepared with chitosan alone, indicating that their biodegradability is enhanced, especially cling film C and cling film D have higher biodegradability.
[0089] Test Example 4 Antioxidant Function Test
[0090] (1) Cut the plastic wrap into small pieces of 20 mm × 20 mm and place them in a 50 mL test tube. Add 4 mL of methanol and place them at room temperature in the dark for 2 h.
[0091] (2) Pipette 3 mL of sample solution and mix with 1 mL of DPPH methanol solution (150 μmoL / L) and place at room temperature away from light for 30 min to allow the reaction to complete;
[0092] (3) Methanol was used as the blank background to adjust the zero value. 3 mL of methanol was mixed evenly with 1 mL of DPPH methanol solution (150 μmoL / L) for reference. The absorbance of the sample solution at 517 nm was measured. Each group was measured three times.
[0093] DPPH free radical scavenging rate (%) = (A0-A1) × 100 / A0
[0094] Where A1 and A0 are the absorbance of the reference and sample solutions, respectively.
[0095] The test results are as follows Figure 1As shown, the cling film A prepared with chitosan alone has weak antioxidant capacity, the comparison film has a certain antioxidant capacity, and the cling films B, C, and D show higher DPPH free radical scavenging rates, indicating that they have good antioxidant function.
[0096] Test Example 5 Mechanical Properties Test
[0097] The cling film was cut into small pieces of 20 mm × 70 mm, and its tensile strength (TS) and elongation at break (EB) were measured using a texture analyzer. The test speed was 50 mm / min, the clamp distance was 40 mm, and the measurement was repeated 4 times for each group of films.
[0098] TS=F / (d×W)
[0099] Where: TS—tensile strength (N / mm 2 ); F—maximum tension when the membrane breaks (N; d—membrane thickness (mm); W—membrane width (mm);
[0100] Elongation at break calculation formula: EB = (L-L0) × 100 / L0
[0101] Where: EB is the elongation at break (%); L is the distance between the marking lines when the film breaks (mm); L0 is the distance between the original marking lines of the film (mm).
[0102] The test results are as follows Figure 2 As shown, the tensile strength of cling film B, C, and D is comparable to that of cling film A and the comparative film prepared using only chitosan. Cling film B, C, and D have good tensile properties at break, especially the elongation at break is increased compared with cling film A and the comparative film prepared using only chitosan.
[0103] Test Example 6 Ultraviolet blocking performance test
[0104] The cling film was cut into small pieces of 10 mm × 40 mm and scanned in the range of 200-800 nm using an ultraviolet spectrophotometer to determine the light transmittance of the cling film.
[0105] The test results are as follows Figure 3 As shown, the cling film B, C, and D have good UV blocking properties and are superior to the cling film A and the control film prepared using only chitosan.
[0106] Test Example 7 Water Vapor Transmission Rate Test
[0107] (1) Measure the thickness of the film (x, m) using a vernier caliper;
[0108] (2) Take a 50 mL beaker and calculate the beaker mouth area, i.e. the effective penetration area (S, m 2 ), and added 20 mL of distilled water thereto;
[0109] (3) Cover the mouth of the cup with a film and fix it with a thin rubber band, put it in a desiccator containing silica gel, and leave it at room temperature;
[0110] (4) Weigh every 2h (Δt, s) to obtain the mass of water permeation (Δm, g), and weigh 6 times. Calculate the water vapor permeability coefficient (WVP, gm -1 s -1 Pa -1 ).
[0111] WVP=(Δm×x) / (S×Δt×ΔP);
[0112] Where x is the membrane thickness, m; Δm is the mass of water permeation, g; S is the effective permeation area, m 2 ; Δt is the interval time, s; ΔP is the pressure difference on both sides of the membrane, 2.945 kPa.
[0113] The test results are shown in Table 4.
[0114] Table 4 Water vapor permeability of cling film
[0115]
[0116] The test results show that the water vapor permeability of cling film B, C, D is comparable to that of cling film A prepared with only chitosan and the control film.
[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a degradable film material, characterized in that: include: Mixing chitosan, gallnut extract, glycerin and organic acid aqueous solution to prepare a degradable membrane material solution; Then, the degradable film material solution is poured into a mold and dried to obtain a product; Wherein, the preparation method of the gallnut extract comprises: After the gallnut is crushed into powder, the gallnut powder is mixed with an alcohol solution in a ratio of 1 g: (8-12) mL, and the mixture is placed at 70° C.-80° C. for more than 60 minutes, and then ultrasonically extracted for 25-35 minutes; the extraction is repeated for more than 3 times, the extracts are combined, and the filtrate is filtered and then dried to obtain a gallnut extract; the concentration of the alcohol solution is 75%-85%.
2. The preparation method according to claim 1, characterized in that: The weight ratio of chitosan to gallnut extract is 1:(0.1~0.3).
3. The preparation method according to claim 1, characterized in that: The weight ratio of chitosan to glycerol is 1:(0.1~0.3).
4. The preparation method according to claim 1, characterized in that: The weight ratio of chitosan to organic acid is 1:(0.4~0.8).
5. The preparation method according to any one of claims 1 to 4, characterized in that The organic acid is acetic acid.
6. A degradable film material, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 5.
7. Use of the degradable film material according to claim 6 in the field of packaging materials.
Citation Information
Patent Citations
Multifunctional chitosan / gallnut tannin blended membrane and preparation method thereof
CN111234324A